Foreign Scientists and Engineers and Economic Growth in Canadian Labor Markets - Giovanni Peri; Kevin Y. Shih (Institute for the Study of Labor (IZA), 2013)
In this paper we analyze the impact of foreign-born workers in the fields of Science, Technology, Engineering and Math (STEM) on employment and wages in Canadian geographical areas during the period 1991-2006. Canadian policies select immigrants with a strong emphasis on high educational attainment. Moreover the foreign-born constitute a third of the Canadian population making Canada a very good case to analyze the effect of foreign-STEM workers on the local economy. We use the dispersion of immigrants by nationality across 17 geographical areas in 1981 to predict the supply-driven increase in foreign Scientists and Engineers during the period 1991-2006. Then we analyze their impact on the employment and wages of college and non-college educated Canadian-born (native) workers. We find significant positive effects on the wages and (to a lesser extent) employment of college educated natives. We also find a smaller positive effect on the wages and employment of native workers with very low levels of education (i.e. those with no high school degree). This implies a positive productivity effect of foreign-STEM workers in Canada, and also a college bias in their contribution to productivity growth. Compared to the effect of foreign Scientists and Engineers in US cities, the Canadian results show similar effects on wages of college educated and at least partial evidence of a positive diffusion of the effect to non-college educated, which was not present in the US.
Keywords: J61; F22; O33; R10; 330; STEM workers; foreign-born; Canadian-born; college-educated; wage; employment